2009
DOI: 10.1111/j.1468-1331.2009.02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in Serbian patients with Wilson disease

Abstract: Despite the relatively early diagnosis and treatment of our patients with WD, mortality was still considerably high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
1
41
3
Order By: Relevance
“…The present study has highlighted different peculiarities of these patients with respect to WD children reported elsewhere. [6][7][8][9]13 The measurement of ceruloplasmin serum levels is also a first-step test for the diagnosis of WD in children with mild liver disease, as demonstrated by the good sensitivity and acceptable specificity of this test at the cutoff of 20 mg/dL in the studied population. Obviously, low levels of ceruloplasmin are not always indicative of a copper storage disorder because both heterozygotes for WD and patients with other disorders may share this feature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study has highlighted different peculiarities of these patients with respect to WD children reported elsewhere. [6][7][8][9]13 The measurement of ceruloplasmin serum levels is also a first-step test for the diagnosis of WD in children with mild liver disease, as demonstrated by the good sensitivity and acceptable specificity of this test at the cutoff of 20 mg/dL in the studied population. Obviously, low levels of ceruloplasmin are not always indicative of a copper storage disorder because both heterozygotes for WD and patients with other disorders may share this feature.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8][9]13 In fact, all the WD patients evaluated in the present study were referred for raised aminotransferases and could be considered asymptomatic or presymptomatic. Therefore, this population represents a valuable specimen for assessing the appropriateness of the WD diagnostic criteria in children with mild liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of death in WD patients treated by LT is an important issue, particularly since several long-term follow-up studies of WD patients subjected to medical treatment have revealed a survival rate quite similar to that of the healthy population except in cases with advanced liver cirrhosis [27][28][29][30] . The high death rate in case reports of LT in WD patients with neurological impairment is worrying (5 of 21 cases).…”
Section: Previous Literature On Lt In Neurologically-impaired Wd Patimentioning
confidence: 99%
“…Another problem is suicide as described Tatsumi et al (11). Suicide may be one of the psychiatric problems due to depression, decreased functional capacity, hopelessness or the need of long-term treatment (16 …”
Section: Wilson Disease Is An Autosomal Recessive Disorder Characterimentioning
confidence: 99%